Suplai DC Terpisah untuk Multilevel Inverter Satu Fase Tiga Tingkat Menggunakan Buck Converter - Warsito, Agung; Facta, Mochammad; A.W., Donny (Departemen Teknik Elektro, Universitas Diponegoro, 2008)
DC chopper or DC to DC converter is a power electronics circuit which convert DC voltage to desired variable DC voltage. This paper presents the making of DCChopper in Buck converter type which is used as separated DC power supply for one phase multilevel inverter in three level. This Buck converter produce variable voltage which can be adjusted by duty cycle control in order to meet one phase multilevel inverter need. Duty cycle is obtained by using pulse width modulation technique with constantÂ frequency range 2 kHz. This separated DC power supply is made from three Buck converter which is consist of three MOSFET as switching components. Triggering signal for MOSFET is produced and controlled by microcontroller AT89S51. This system is made in open loop with one phase multilevel inverter as the load. As a result, this DC chopper is able to supply multilevel inverter with duty cycle varitation for the first and third stage Buck converter is 20%Â - 65%, and 50% - 95% for the seccond stage Buck converter.Key words:Â buck converter, duty cycle, multi-level inverter, PWM, mikrokontroller